Kepemimpinan Profetik Kepala Sekolah dalam Kinerja Guru Studi Kasus SMP Jam’iyyatut Tholibin Kandangan dan MTS Mu'allimin Mudal Temanggung - Irfani, Ahmad; Nursikin, Mukh (LPPM Institut Pendidikan Nusantara Global, 2024)
An indicator of the success of a school principal's leadership that can be guaranteed to achieve school goals is leadership that is based on the leadership of the Prophet Muhammad. The success achieved by the Prophet Muhammad SAW during his leadership is strongly thought to be because the pattern that was built was based on love, example, faith and devotion to Allah SWT. This research method uses a descriptive qualitative approach with a phenomenological type involving informants from Foundation Management, School Committee Management, school principals, teachers and staff. Data collection used was observation, interviews and document study. The results of the research found that the Principal's Prophetic Leadership in Teacher Performance at Jamiatul Tholibim Kandangan Temanggung Middle School was adapted to the grand design that had been prepared by the Principal including, communicating the school's vision and mission, organizing activities based on the school's strategic plan, entrusting the work team to work in accordance with their fields. responsibility, enlivening and cultivating faith values, holding joint evaluations in accordance with mutual agreement, to reflect and internalize the meaning of each activity that has been carried out. Driving factors are the Principal's Vision and Commitment, Support from the School Committee and Foundation, Teacher Involvement in Positive School Culture Decision Making. The inhibiting factors are resistance to change and lack of resources.